Diagnostic performance of 18F‐fluorodeoxyglucose positron emission tomography in the evaluation of glioma. Issue 5 (1st August 2019) - Shaw, Tristan B; Jeffree, Rosalind L; Thomas, Paul; Goodman, Steven; Debowski, Maciej; Lwin, Zarnie; Chua, Benjamin
Abstract: Introduction: Identifying glioma grade through imaging allows clinicians to recommend and accurately direct treatment. We sought to quantify the utility of FDG‐PET/CT (18F‐fluorodeoxyglucose positron emission tomography/computed tomography), alone and in combination with MRI, in identifying high‐grade regions of glioma. Methods: This is a retrospective review of patients who had an FDG‐PET/CT performed as part of the workup of suspected glioma or in follow‐up of known glioma. FDG‐PET/CT scans were reviewed and uptake in the identifiable lesion coded as none, diffusely or focally increased. Patients also underwent gadolinium‐enhanced MRI, noting regions of contrast enhancement. Sensitivity, specificity, positive and negative predictive values (PPV and NPV) were calculated for identification of high‐grade histology (WHO III or IV, or metastatic disease) obtained post‐FDG‐PET/CT. Results: Thirty‐three patients had 36 FDG‐PET/CT and MRI scans followed by histological confirmation (biopsy or debulking). Increased FDG uptake demonstrated a sensitivity of 59% and specificity of 79%, PPV of 81% and NPV of 55% for identification of high‐grade histology. MRI demonstrated a sensitivity of 77% and specificity of 86%, PPV of 89% and NPV of 71% for identification of high‐grade histology. Only 64% of MRI and FDG‐PET/CT scan series were concordant. When FDG‐PET/CT and MRI were concordant, a specificity of 100% and PPV of 100% was achieved, however, sensitivity was 79% and NPV was 75%. Conclusion: The combination of FDG‐PET/CT and gadolinium‐enhanced MRI demonstrated marked improvement in identifying potential high‐grade disease over each modality alone. Increased FDG uptake without gadolinium enhancement rarely occurred and identified high‐grade histology in a small number of patients. Due to limited sensitivity and NPV, a negative FDG‐PET/CT alone, or in combination with MRI, should not guide a decision for observation where surgery would otherwise be recommended.